Reading women's stories : female characters in the Hebrew Bible - Petersen, John (Professor) (Minneapolis, MN : Fortress Press, 2004)
"...delves deeply into three stories of women in the Hebrew Bible (Hannah, Deborah, and Tamar) and explores issues of reading character, plot, and point of view"--P. 4 of cover.
Includes bibliographical references (p. 217-226).
Keywords: Hannah -- (Biblical figure); Deborah -- (Biblical judge); Tamar, -- daughter-in-law of Judah; Bible. -- Criticism, Narrative; Women in the Bible